Soil quality indicator of oxisols grown with sugarcane and native forest in northeastern São Paulo state, Brazil - de Freitas, Ludmila; Filho, Marcílio Vieira Martins; Casagrande, José Carlos; de Oliveira, Ivanildo Amorim; da Silva, Luiz Gabriel (Springer Nature, 2018)
The evaluation of soil quality is an important tool for degradation monitoring and sustainable management implementation. The objective of this study was to measure physical and chemical soil properties to set soil quality and validate a model of soil quality indicator in latosols (oxisols) under sugarcane cropping and native forest. The study was carried out in the cities of Araras, Santa Ernestina, and Guariba in São Paulo State, Brazil. We collected 24 samples of disturbed and undisturbed soil at 0.0–0.10 m layer from three areas grown with sugarcane and neighboring locations under native woodland. We assessed the following soil properties: (a) chemical—pH in CaCl2, organic matter (OM), phosphorus (P), potassium (K+), calcium (Ca2+), magnesium (Mg2+), potential acidity (H + Al), aluminum (Al3+), and sulfur (S); (b) physical—macro- and microporosity, soil bulk density (Ds), aggregate stability, mean weight diameter (MWD), rill (Kr) and interrill (Ki) global erodibility, shear stress (τc), and magnetic susceptibility (MS). Data underwent multivariate statistics to identify the properties that denote soil quality and to set their weights within the functions of soil quality indicator (SQI). This study showed that the multivariate analysis was efficient in determining which physical and chemical properties were most sensitive, of which we can mention total sand, MS, clay, microporosity, Mg, Ca, pH, and OM. We can therefore conclude that the quality indicators of soils grown with sugarcane were lower than those under forest were, showing the need for adoption of conservation management practices.
Keywords: Multivariate statistics; Oxisols; Soil properties; Weighted additive model